Pengembangan metode perancangan konsep produk sukses berdasarkan pertimbangan kebutuhan subjektif berbagai etnik - , Imam Djati Widodo ([Yogyakarta] : Fakultas Teknik Universitas Gadjah Mada, 2013)
The product success and failure study is very important because it is related to the increase of company profit, market share and reputation. Though this study has been underlined by most companies and identified need high cost for researh and development, data showed that the product failure rate was still high. Based on the problem, this research tried to formulate product success/failure measure method, identify success/failure factors for each context, and develop product design and forecasting method. This research was divided into three steps. The first step was related to developing product success determination. Measurement method was developed and used to select the products that would be analyzed in the following discussion. The second step was to identify factors that significantly related to product success for each context product segmentation and culture. . The last step was to develop product design and forecast method based on some factors in each context found in the previous step. The objects of this research were mobile phone, motorcycle, and car. This research involved three ethnics